Validity and reliability of a commercial fitness watch for measuring running dynamics - Adams, D.; Pozzi, F.; Carrol, A.; Rombach, A.; Zeni, J. (Journal of Orthopaedic & Sports Physical Therapy, 2016)
Study Design: Validity and reliability study.